FENOMENA DEINDIVIDUASI DALAM AKUN ANONIM BERITA GOSIP SELEBRITI DI MEDIA SOSIAL INSTAGRAM - Ari Wicaksono; Irwansyah Irwansyah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
The phenomenon of deindividuation is a phenomenon that occurs in a society where the level of individual identity begins to decline and encourage the individual to join a group. In relation to the deindividuation phenomenon that occurs in Instagram, this research has purpose to review the effects of anonymous account of celebrity gossip news either to its follower or its surround environment. Using the deindividuation theory, anonymous accounts of celebrity gossip news have a significant role: it has an appeal compared to the official